10 Empowerment and education for family carers supporting someone at end-of-life: an evaluation of hospice-led community sessions. (30th January 2023) - Wright, Louise; Faull, Christina; Smith, Penny; Birt, Linda
Abstract : Introduction: Family carers supporting a person through the last year of life have specific concerns, including living with anticipatory grief, understanding stages of dying and practical responsibilities post death. Hospice staff are ideally situated to enable carers to understand the emotional and practical aspects of end-of-life. Aims: Responding to community need LOROS hospice education team developed a bespoke family carers empowerment and education training package. The project was designed in collaboration with carers and a stakeholder group of carers organisations. Evaluation is ongoing to access the feasibility, utility and scalability of the project. Methods: Using the plan, do, check, act model, five family carers and the stakeholder group were consulted to identify carers needs. Grounded in the literature and this data, the hospice education team developed an eight-hour training package. The training was run over four two-hour sessions at a carers group in a community hall in Leicester. This presentation will summarise the full delivery and evaluation cycle, including next steps Results: Consultations with carers indicated that venue and timing of sessions was important. Consultees said carers wanted practical information on how to recognise someone was dying and legal requirements surrounding death. They would like signposting to information and discussions on how to manage their own wellbeing. Importantly family carers told us to not spend too long 'talking about what to do' but to 'get on and do it'. Conclusions: The plan, do, check and act model ensures that training is tried, evaluated and modified. Early results indicate that carers value the sessions, but only small numbers are attending Impact: Evaluating strengths and limitations of training for carers means future provision can consider ways to increase access and relevance for family carers.